Self-Assessment on Capacity Gaps and Readiness in Attaining National Accreditation for Ethics Committees under Ministry of Public Health of Thailand - ประคองสาย ภูษิต; รัชตพันธนากร เบญฑิรา; จงศิริ มยุรี (Journal of Health Science of Thailand, 2020)
Roles of ethics committees are to protect the rights, safety, and well-being of human participants or volunteers in joining a research project. The goal of the Ministry of Public Health of Thailand is to develop a system for standardizing ethics committees that conforms to the national and international ethical standards. This quantitative research aimed at investigating the situation and assessing capacity gaps and readiness of ethics committees of health facilities and institutes under Office of Permanent Secretary, Ministry of Public Health, Thailand using a self-assessment form developed by the National Ethics Committee Accreditation System of Thailand (NECAST). The self-assessment form consists of 5 dimensions of standards with 15 aspects. Data was collected through a self-administered questionnaire survey from January to March 2018. The study revealed that organizations responding the NECAST self-assessment form consisted of 33 provincial public health offices (35.1%), 29 general hospitals (30.9%), 16 regional hospitals (17.0%), 15 Boromrajonani Colleges of Nursing (16.1%), and 1 College of Public Health (1.0%). Most Boromrajonani Colleges of Nursing, regional, and general hospitals (87.5, 64.3, and 100%, respectively) achieved readiness in Standard 2: Adherence to specific policies, Aspect 2.1: EC management. Regional hospitals, Boromrajonani Colleges of Nursing, provincial public health offices, general hospitals, and College of Public Health (13.3, 9.0, 0.0, and 0.0, respectively) met the minimum requirements for Standard 1.3: training of EC members, and structure and compositions of EC (membership requirements), particularly in providing for its members to receive introductory training and continuous education. Out of 94 organizations, only one Boromrajonani College of Nursing met the whole requirements and had readiness in the 5 dimensions of standards with 15 aspects. In conclusion, the capacity gaps of the ethics committees under Office of Permanent Secretary, Ministry of Public Health that need to be improved urgently were training and capacity strengthening of EC members, and management of the organizational structure and composition of EC members.